Influence of light irradition and heat treatment on the optical properties of amorphous As45S15Se40 thin films - Iovu, Mihail (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2011)
The experimental investigation of the influence of the light irradiation and heat treatment on the optical parameters of one of highest sensitive chalcogenide glass As45S15Se40 was investigated. For the amorphous As45S15Se40 thin films prepared by „flash” thermal evaporation, from the transmission spectra the value of the refractive index n was found n = 2.921 at λ = 650 nm, and the optical band gap Eg was determined from the Tauc plot Eg = 1.929 eV. From the dispersion curves of the refractive index n = f(λ) and (n2-1)-1 = f(hv), by fitting a straight line to the experimental points, the single-oscillator energy E0 and the dispersion energy of oscillator strength Ed were estimated. The kinetics of photodarkening in amorphous As45S15Se40 thin films is described by a stretch exponential function, and the effect at illumination with laser beam λ = 540 nm is more pronounced than in amorphous As2S3 and As2Se3 films. The maximum of the diffraction efficiency λ of the holografical gratings recorded during the exposure of laser beam at λ = 540 nm is reached at about t = 250 s.